Abstract 218: Evaluating Thrombectomy Candidacy in Large Core Strokes: Lessons from the SELECT2 Trial at Our Institution - Mohammad Khasawneh; Eve Moll; Brendan Eby; Laura Heitsch (Stroke: Vascular and Interventional Neurology)
Introduction Reperfusion therapy for patients with large vessel occlusion stroke includes thrombolytics and mechanical thrombectomy. Candidacy for thrombectomy depends on patient factors under active investigation. Historically, patients with large strokes have been excluded from major trials evaluating thrombectomy due to concern that thrombectomy would pose considerable risk with limited benefit. However, new evidence from the Select‐2 Trial found improved modified Rankin scale scores and higher rates of functional independence at 90 days following large stroke in patients who underwent thrombectomy versus medical therapy alone. We explored if patients presenting with large stroke at our institution resemble those in the Select‐2 Trial and, how many previously excluded patients could have possibly benefitted from thrombectomy. Methods Patients presenting as a code stroke at our institution from 1/2022 to 7/2022 were retrospectively analyzed. Large strokes, defined as CTP volume greater than 50mL, were identified. Background information included age, sex, race, and prior stroke. Regarding patient stroke presentation, the following data were gathered: NIHSS, LVO status, CTA results, CTP, tPA, thrombectomy status, TICI score, and discharge status. Our patients included in this study were compared to the patients included the Select‐2 Trial. Mortality rates and NIHSS at discharge were compared between thrombectomized and non‐thrombectomized patients at our institution. Results Of the 365 code strokes activated at our institution during the study period, 26 met criteria for a large stroke. Of those 26, 13 met all criteria for inclusion in SELECT‐2. Only 9 of the 26 patients received thrombectomy, including 7 of 13 patients otherwise meeting SELECT‐2 criteria. 6 patients were excluded from thrombectomy who would have met criteria for SELECT‐2. Of the 9 who underwent thrombectomy, one expired, and the average NIHSS calculated from physical exam at discharge of surviving patients was 13. Of the 17 who did not undergo thrombectomy, seven expired and the average NIHSS at discharge was 19.4. Of large stroke patients, average age was 69.5 years (SD 11.0), similar to Select‐2 (median age 66). Average NIHSS at presentation was 19 (SD 6.55), similar to Select 2. Compared to SELECT2 enrollment, our patients were more likely to be female (50% vs 41%), Black (50% vs 25%), have a history of prior stroke (38% vs. 9%). LVO was identified on 23 of 26 patients. Of these 23, 17 MCA, 3 ACA, 6 ICA, and 2 carotid terminus occlusions were identified (6 had tandem occlusions). The average rCBF volume was 102.3 mL (SD 64.3) compared to median estimated ischemic core volume of 80mL in Select 2. Conclusion The patients presenting to our institution with large stroke resemble those included in the Select 2 trial, which demonstrates positive outcomes following mechanical thrombectomy for this special population. Patients with large strokes are frequently excluded from receiving treatment with mechanical thrombectomy. Analysis of a larger data set, including large stroke patients from 2018 to 2022, is currently pending. In light of the Select 2 trial, patients in our community and in our referral basis stand to benefit from an institutional practice of offering thrombectomy to those presenting with large stroke.